Effects of application phytostim biostimulant on growth, yield postharvest quality, and metabolites of two amaranth species - Magwele, Mapula Precious (My University, 2024)
Amaranthus species are indigenous crops in South Africa, commonly consumed as leafy vegetables. It has been consumed for many decades by the rural community population for its nutritional and nutraceutical properties. However, the crop is still not commercialized due to limited productivity in the country. There is scant information on the cultivation of Amaranthus species and its improvement as compared to the exotic crops such as spinach and lettuce. Thus, it is pertinent to find ways of improving the crop in terms of yield, and postharvest quality attributes. This study was aimed at establishing the information on the effect of different concentrations of Phytostim® biostimulant on growth, yield, and postharvest quality of Amaranthus cruentus and Amaranthus caudatus. The objectives of this study was to (1) investigate the effects of different concentrations of Phytostim® biostimulant on growth and yield attributes, (2) to investigate the interactive effect of Phytostim® biostimulant concentrations and storage period on postharvest shelf life quality attributes, nutritional components, and secondary metabolites of the two Amaranthus species. The different concentrations of Phytostim® biostimulant used in this study were 0, 0.5, 1, 1.5, 2.5, 3, 4.5, and 6% while untreated plants (0%) were used as control in all the objectives. To achieve objective one: four-week-old seedlings of Amaranthus species were grown in a greenhouse condition following a Randomized Complete Block Design (RCBD) for a period of eight weeks (60 days). Different concentrations of Phytostim® biostimulant were foliar-applied after every 14-day until harvest. Growth and yield attributes (stem diameter, plant height, number of branches, number of leaves per plant, fresh and dried leaf mass per plant) data were collected at harvest. It was observed that Phytostim® biostimulant significantly affected (p<0.05) growth and yield attributes of amaranth. On the growth attributes, Phytostim® biostimulant increased the plant height by 97 cm and 110 cm at 1.5 % concentrations in both Amaranth species. While on the stem diameter increased by 13 mm and 17 mm. On the number of branches, it increased by 30 and 44. On yield parameter, highest biomass obtained was 74.23 g and 85.93 g per plant. On the second objective: the harvested leafy vegetables of amaranth were separated into uniform bundles of 100 g weight in a well-ventilated punnet and stored at ambient temperature for 0, 3, and 6 days for assessment of weight loss, color, and visual quality. During these storage period, a total of 5 g per replicate was sampled at three days intervals and oven dried at 40 ºC for 72 h for analysis of nutrient components and secondary metabolites such as mineral elements, amino acids, protein, and phenolic compounds. It was observed that Phytostim® biostimulant and storage days significantly affected (p<0.05) some of postharvest quality and nutritional components of amaranth. Weight loss in 2.5% biostimulant was 20.85%, and 30.89% at day 6 in A. cruentus and A.caudatus. These in terms of color, the leaves that maintained a good color quality was at 0.5 % (h° = 148.21 and a*= -12.29) for A. cruentus. At the end of storage period (6d) the leaves maintained a good color quality was at 2.5% (h° = 124.14 and a* = -10.66) in A. caudatus. The obtained results revealed that weight loss%, color, and visual quality of amaranth were significantly (p<0.05) influenced by different concentrations of Phytostim® biostimulant and storage time. All the above-mentioned postharvest attributes were improved at 2.5% concentrations of Phytostim® biostimulant in comparison to control. Moreover, the study further revealed that different concentrations of Phytostim® biostimulant significantly (p<0.05) influenced the mineral elements (Mg, Ca, Fe, K, Zn, N, Cu, Se, and Mn), amino acids (His, Leu, Lys, Met, Phe, Thr, Val, Ala, Arg, Asp, Glu, Gly, Pro and Ser) and protein content of the studied leaves. The nutrients components were enhanced at 2.5% concentrations of Phytostim® biostimulant as compared to the control and other concentrations of Phytostim® biostimulant. Thus, it can be concluded that Phytostim® biostimulant can be recommended to be used effectively by farmers at 2.5% for up to 6 days or less in preserving the high-quality characteristics of Amaranth species during ambient temperature. On the last stage of this study, the untargeted phenolic compounds were determined using the Liquid Chromatograph Mass Spectrometer (UPLC-MS). A total of 12 phenolic compounds were detected in the studied leaves. Phenolic compounds of the treated plants were significantly higher in comparison to the phenolic compound of the untreated plants. Principle Component Analysis and Orthogonal Partial Least Squares-Discriminant Analysis showed that Phytostim® biostimulant is the main factor responsible for the variation in the studied crop. The major identified phenolic metabolites were members of the coumarin glucoside, glucuronic acid, and flavonoid-3-glycosides. Predominant phenolic compound quantified was rutin in both species. This objective spotted Phytostim® biostimulant concentrations at 3% to be the best for enhancing secondary metabolites. Therefore, overall recommendation these objectives suggest that Phytostim® biostimulant concentrations starting from 1.5% up to 3% could be used to improve the yield, nutrients, and secondary metabolites.
Thesis (M. Agricultural Management (Plant Production)) -- University of Limpopo, 2024
Keywords: Phytostim biostimulant; Growth yield; Postharvest quality; Metabolites; Amaranth species; Amaranths; Edible greens; Metabolites; Crops -- Postharvest technology